Deskripsi Pembelajaran Bermakna Pada Praktikum Kimia Dasar Mahasiswa Pendidikan Kimia - Sri Lestari; Erlina; Ira Lestari; Masriani; Maria Ulfah (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to describe meaningful learning in basic chemistry practicum of chemistry education students of FKIP UNTAN. The method used in this research is quantitative descrptive method. Quantitative data were collected using Meaningful Learning in the Laboratory Instrument (MLLI) instrument to measure students’ affective and cognitive experiences after learning in the laboratory. This study also used interview guidelines to collect more in-depth information about meaningful learning experiences for chemistry education students in basic chemistry practicum courses. This study involved 51 first semester students of Chemistry Education of FKIP UNTAN who had completed basic chemistry practicum courses, laboratory heads, laboratory assistants,and lecturers teaching basic chemistry practicum courses. The results showed that all aspects were rated as good. With percentage scores of 67% for affective aspects, 75 % for cognitive aspects, and 67% for affective-cognitive aspects, resulting in an overall average score percentage of 72%. Based on these findings, it shows that first semester chemistry education students have achieved good meaningful learning trough their learning experiences in basic chemistry practicum.